2004
DOI: 10.1038/sj.ejhg.5201282
|View full text |Cite
|
Sign up to set email alerts
|

Single-nucleotide polymorphisms in genes relating to homocysteine metabolism: how applicable are public SNP databases to a typical European population?

Abstract: To facilitate the association studies in complex diseases characterized by hyperhomocysteinemia, we collected structural and frequency data on single-nucleotide polymorphism (SNPs) in 24 genes relating to homocysteine metabolism. Firstly, we scanned B1.2 Mbp of sequence in the NCBI SNP database (dbSNP) build 110 and we detected 1353 putative SNPs with an average in silico genic density of 1:683. Out of 112 putative SNPs in coding regions (cSNPs), we selected a subset of 42 cSNPs and we assessed the applicabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…Hcy is a product of demethylation of essential amino acids and is degraded via transsulfuration or remethylation pathways (Castro et al 2006). Thus the co-factors and enzymes involved in these pathways have been the main focus of studies to assess the inXuence of allelic variation on circulating hcy (Fredriksen et al 2007;Janosikova et al 2005;Frosst et al 1995). These investigations have highlighted the importance of the MTHFRg.677C > T sequence alteration in determining plasma hcy but have shown inconsistent Wndings with other allelic variations (Fredriksen et al 2007).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Hcy is a product of demethylation of essential amino acids and is degraded via transsulfuration or remethylation pathways (Castro et al 2006). Thus the co-factors and enzymes involved in these pathways have been the main focus of studies to assess the inXuence of allelic variation on circulating hcy (Fredriksen et al 2007;Janosikova et al 2005;Frosst et al 1995). These investigations have highlighted the importance of the MTHFRg.677C > T sequence alteration in determining plasma hcy but have shown inconsistent Wndings with other allelic variations (Fredriksen et al 2007).…”
Section: Discussionmentioning
confidence: 97%
“…Family studies suggest that this sequence variation is only responsible for a proportion of the genetic variability impacting on plasma hcy, with a number of other genes also likely inXuencing hcy (Jee et al 2002;Souto et al 2005). Most investigations of the genetic determinants of hcy have focused on genes involved in one carbon metabolism (Janosikova et al 2005;Fredriksen et al 2007). The nuclear transcription factor peroxisome proliferator-activated receptor-gamma (PPARG) controls a large number of metabolic pathways under the inXuence of both endogenous and pharmacological ligands (Sharma and Staels 2007).…”
Section: Introductionmentioning
confidence: 97%
“…In the largest study carried out so far, Fredriksen et al 12 genotyped a large population of Norway for 13 SNPs present in 1-carbon metabolism genes and found that methylenetetrahydrofolate reductase (MTHFR C677T and MTHFR A1298C), 5-methyltetrahydrofolate-homocysteine methyltransferase (MTR A2756G), and cystathionine ␤ synthase (CBS 844_845ins68 and CBS C699T) are associated with homocysteine levels. Janosikova et al 13 apparently genotyped healthy individuals from Czechoslovakia in an attempt to obtain the frequency of 42 SNPs in genes involved in 1-carbon metabolism, but no attempt was made to evaluate their effect on homocysteine levels. The situation in India is even worse as there has been no attempt made to even analyze the basal frequencies of SNPs in genes involved in 1-carbon metabolism, despite the fact that India accounts for one sixth of the world population.…”
Section: Clinical Perspective On P 606mentioning
confidence: 99%
“…Forty-four nsSNPs were chosen for the study from the genes involved in homocysteine metabolism either from dbSNP or from the study by Janosikova et al 13 These selected SNPs were scored using the SNaPshot ddNTP primer extension kit (Applied Biosystems, Foster City, Calif), as described earlier. 11 …”
Section: Snapshot (Minisequencing)mentioning
confidence: 99%
“…These transversions occur at the lowest frequency (approximately 7%) of all SNPs (36 ) and represent Ͻ3% of SNPs found in coding regions of 24 genes related to 1-carbon metabolism (37 ). An expected advantage of mass-modified ddNTPs with respect to our assay was the elimination of mass interferences by ammonium adducts.…”
Section: Terminatorsmentioning
confidence: 99%